'Bulldozers aren't just for boys': respectful relationships education challenges gender bias in early primary students. Issue 4 (4th July 2022) - Ollis, Debbie; Iannucci, Cassandra; Keddie, Amanda; Holland, Elise; Delaney, Maria; Kearney, Sarah
ABSTRACT: Addressing respect, gender equity and gender-based violence in schools has a long history. Renewed government efforts to address gender-based violence in schools through a whole school approach have commenced under the umbrella 'respectful relationships education'. The research presented in this paper is nestled within a larger project aimed to evaluate the implementation and impact of a whole school approach to respectful relationships education across two Australian states (Our Watch, forthcoming). The purpose of this paper is to examine the effects of a six-month respectful relationships education program on the gender awareness and bias of early primary school students. Using a single group pre-post test research design, students from two primary schools in Australia completed a survey before (n = 202) and after (n = 217) completion of a respectful relationships education pilot program. A modified version of the Children's Occupation, Activities, and Traits-Attitudes Measure (COAT-AM; Liben and Bigler, 2002) and the Children's Occupation, Activities, and Traits-Personal Measure (COAT-PM; Liben and Bigler, 2002) were used to assess students' views about gender. After the pilot, boys and girls were significantly less likely to consider stereotypically masculine occupations and activities as only for boys and stereotypically feminine occupations and activities as only for girls. Results indicate that ongoing respectful relationships education could be an effective way to disrupt gender stereotyping in early primary school students.